Atypical psychotic symptoms and Dandy–Walker variant. Issue 5 (2nd September 2016) - Williams, Aislinn J.; Wang, Zhenni; Taylor, Stephan F.
ABSTRACT: New-onset psychotic symptoms often respond well to antipsychotic treatment; however, symptoms may be difficult to treat when an underlying brain malformation is present. Here, we present a case of atypical psychotic symptoms in the context of a congenital cerebellar malformation (Dandy–Walker variant). The patient ultimately improved with paliperidone palmitate after multiple antipsychotic medication trials (both oral and one long-acting injectable) were ineffective. Neuroimaging may provide valuable diagnostic and prognostic information in cases of new-onset psychosis with atypical features and treatment resistance, even in the absence of neurologic signs and symptoms.